2008
DOI: 10.33899/magrj.2008.26581
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF HIGH LEVELS OF NITROGEN AND PHOSPOURS FERTILIZER, PINCHING, AND SEED RATE ON GROWTH AND YIELD COMPONENTES OF Nigella sativa L.

Abstract: Field experiment was conducted during the season [2005][2006] in Singar -Mosul city to investigate the effects of high level (280 N, 260 P 2 O 5 ) kg ha -1 and very high level (320 N, 300 P 2 O 5 ) kg ha -1 fertilizer, pinch and without pinch, and plant seed rate sowing (0.6, 0.8, 1.0, 1.2) g/10m 2 cultivated within 3, 4, 5, 6 rows respectively in (10) m 2 plot area on growth and yield of Nigella sativa L. The experiment was laid out in randomized complete block design with three replications. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…It is quite clear from the data in Moreover, pinching causes a significantly increased in fruits number of black cumin compared to un-pinched plants [28]. Kumar et al [6] reported that stevia plants pinched at 40 days after transplanting recorded significantly higher number of leaves per plant, fresh leaf weight at 1 st harvest and about 27.7% higher total dry biomass of leaves as compared with control.…”
Section: Yield Componentsmentioning
confidence: 87%
“…It is quite clear from the data in Moreover, pinching causes a significantly increased in fruits number of black cumin compared to un-pinched plants [28]. Kumar et al [6] reported that stevia plants pinched at 40 days after transplanting recorded significantly higher number of leaves per plant, fresh leaf weight at 1 st harvest and about 27.7% higher total dry biomass of leaves as compared with control.…”
Section: Yield Componentsmentioning
confidence: 87%
“…Black cumin, Nigella sativa L. is an annual herbaceous plant belonging to the family Ranunculacea (Hammo, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Black Cumin (Nigella sativa L.) is an annual herbaceous plant belonging to the family Ranunculacea [1] It is one of the seed spices grown in Ethiopia having a commercial demand both in the domestic as well as in the international market. It is one of crops chosen in the specialization program to be produced by selected potential areas.…”
Section: Introductionmentioning
confidence: 99%